Feedback on the usage of flipgrid as platform for short video assignment / Azianti Ismail and Aslina Omar - Ismail, Azianti; Omar, Aslina (UiTM Cawangan Johor Kampus Pasir Gudang, 2020)
The world has been surprised by the COVID-19 pandemic. Teaching and learning activities have changed tremendously. Alternative online platforms have been used to cater to the need in assessing the affective domain activities such as presentations, discussions and group projects. Therefore, this paper intends to share the feedback on the approach of online assessment for the affective domain using Flipgrid as a platform for short video assignment. One of the amazing and useful online apps for video assignment that captured students’ verbal responses. This app helps the students to take part in the learning process, especially in the affective domain. The process of learning to portray an idea or concept, and to convert into own understanding is the learning outcome. This paper explains the students’ feedback on the usage of flipgrid for short video assignment. Feedback process was carried out by using questionnaires to gauge students’ satisfaction and their experience. The advantages of flipgrid are easily downloadable by any user to a mobile device.